Gender and Geographic Trends Amongst Foot & Ankle Surgeons: Where Are We and Where Do We Need to Improve?. Issue 1 (January 2022) - Okereke, Robyn; Janney, Cory; Rezvani, Aryan; Safavi, Kiya Shazadeh
Category: Other Introduction/Purpose: Clinical and elective experiences as well as the guidance of mentors are all critical factors in the pursuance of orthopedic residencies and fellowships. Women have historically been underrepresented in orthopedics. Some propose that the root cause lies in the lack of availability in the aforementioned factors. Previous studies demonstrated geographic differences in sex representation in orthopedic residency programs. Studies over geographic distributions of orthopedic foot and ankle (OFA) surgeons showed high variation in geographic density of OFA surgeons throughout the U.S. This study seeks to determine both the gender and geographic distributions of OFA surgeons as well as to determine geographic patterns between their training locations and current practices. Methods: AOFAS data regarding fellowship completion from 1988 through 2021 was analyzed with regards to gender and fellowship location. Internet searches were performed for all those identified within the database for their medical school, residency, and current practice location. This biographical data was obtained from their front-facing biographical webpage or hospital affiliation. States were placed into regions and subsequent divisions as defined according to the US Census Bureau definition: Northeast (New England and Middle Atlantic), Midwest (East North Central and West North Central), South (South Atlantic, East South Central, and West South Central) and West (Mountain and Pacific). Results: 1, 088 OFA surgeons were analyzed. 168 (15.3%) were female and 922 (84.7%) were male. Female-held OFA fellowship positions increased over time, currently sitting at 13 (22% of all fellowship positions), with a maximum of 15 (25%) in 2017. Geographically, the Pacific had most females (n=26, 15.6% of females), while East South Central had least (n=10, 6.0%). The South Atlantic had most males (n=193, 20.9% of males) while East South Central had least (n=59, 5.3%). The region with the most OFA surgeons in total was the South Atlantic (n=218, 20.0% of the total) whereas the regions with the least were East South Central and New England (n=59, 5.4% in each). Conclusion: Although the amount of female OFA surgeons has increased, the numbers are still low. Geographically, the East South Central division of the U.S consistently had the least number of OFA surgeons whereas the South Atlantic division had the highest.